An Investigation of Shopping Mall Design Requirements - Hasan Burak Çavka (Engineering Proceedings, 2023)
Shopping malls may be considered as controversial structures since they sometimes fail to comply with the expectations of the project stakeholders throughout the project life cycle. New mall projects often attract the attention of people since such a structure has a potential to reshape the neighborhood it is located in; however, the impact is usually negative. On the other hand, the parties involved in mall projects may be subject to criticism from both the public and the industry during the design, construction, and operation. In this study we conducted semi-structured interviews with five managers of an international company that provides real estate services worldwide, and mainly focuses on managing shopping centers within the context of Turkiye. During the interviews, we collected insights on shopping mall design and criteria that have an impact on the operational success or failure. We analyzed the interview data to understand the shopping mall design requirements from the experts’ perspectives. We summarized our investigation under three main categories as location, shop and brand mix, and design. Analyzed data indicates that the requirements and use of shopping malls evolve and change over time. The change is driven by things such as changing habits and expectations of the users and new marketing approaches. Understanding such changes is essential for designers and investors to propose new design approaches and space compositions in order to be able to adapt to the changes. Through our analysis of the collected data, we provided insights on requirements and new trends that affect the design of malls. As further explained in this paper, our analysis indicates a number of important topics during design such as the need to design to fit ever-changing spatial needs, providing feel-good environment for users, correct placement of spaces and stores related to each other, designing circulation that supports commercial activities, and designing with a consideration of operation and maintenance. According to the collected data, the trend of shopping mall design is towards integration of hybrid uses, free forms, more open spaces, increased emphasis on gastronomy, and enabling socializing while leveraging technology and being more sustainable.